Coordinating Effective Field Experiences: Recommendations for Cooperating Teachers. Issue 3 (24th March 2018) - McEntyre, Kelsey; Baxter, Deborah; Richards, K. Andrew R.
Abstract : The role of the cooperating teacher is an integral component of field-based teacher education because the cooperating teacher can bridge the gap between the knowledge developed on campus during physical education teacher education and preservice teachers' field-based learning experiences leading up to and including student teaching. In order to understand the function of the cooperating teacher, it is necessary to evaluate the relationship between cooperating teachers, preservice teachers, and physical education teacher education faculty members. Through the lens of occupational socialization theory, the purpose of this article is to explore best practices for coordinating field experiences with a focus on the role of the cooperating teacher. A conceptual model for understanding how coordinated efforts promote successful socialization is provided, and practices for effective supervision are discussed. The importance of congruence between the cooperating teacher and teacher education faculty members is stressed through this process.